4x-3(x+1)=7

Simple and best practice solution for 4x-3(x+1)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3(x+1)=7 equation:


Simplifying
4x + -3(x + 1) = 7

Reorder the terms:
4x + -3(1 + x) = 7
4x + (1 * -3 + x * -3) = 7
4x + (-3 + -3x) = 7

Reorder the terms:
-3 + 4x + -3x = 7

Combine like terms: 4x + -3x = 1x
-3 + 1x = 7

Solving
-3 + 1x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 1x = 7 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 7 + 3
1x = 7 + 3

Combine like terms: 7 + 3 = 10
1x = 10

Divide each side by '1'.
x = 10

Simplifying
x = 10

See similar equations:

| 4s-27=7(s-4) | | -4(6-x)+4=4-6(x+2) | | 48-2x=7x+23 | | 5-(4-a)=2a | | -14n+16=-12n-16 | | 5x-7=3x+15 | | 140-5x=31+16 | | 3(q+4)+4q+1= | | 7(2v+1)-3(9v+2)=40 | | -9=517n | | 3-2(x-2)=10 | | 8-7x=178-42x | | x+8000=70006 | | 8x+23-4=36 | | 4x+21=14x-29 | | x+8000=7000642 | | 4x+8=38 | | x-12=5x-4 | | 3t-5=7+9t | | 4(5t+3)=24 | | 2x+4/3=8 | | 2x+4/4=8 | | 3(6+c)=2(c-5) | | x^2(x^7)(x^11)= | | 7-5x=4x-11 | | 9(6c-1)-14=52c+9 | | 9(3x+6)=(x-2) | | 52x^2+5x-100=0 | | 5(y-2)=2y-31 | | 20(c+-50)=19000 | | 2-5x=18+3x | | 9x+8=7x+36 |

Equations solver categories